Innovative approaches to strengthen the financial resource base of commercial banks in the context of digitalization - Khaitboyeva Dilnoza Abduvohid qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the current state of commercial banks’ financial resource base development in Uzbekistan under the conditions of digitalization. It highlights the challenges that hinder the expansion of digital financial services, including lack of trust, infrastructure gaps, and regulatory limitations. Based on foreign experien ces and the local context, the author proposes practical strategies for strengthening banks’ financial bases through digital tools, fintech collaboration, and customer-centric innovations.